Digitalisasi Persuratan sebagai Solusi Peningkatan Efisiensi dan Keamanan Dokumen di MTs Expga Univa Medan - Alfa, Lutfiah Malaya; Alyani, Filza; Puspita, Dhea; Atiah, Nur; Darmansyah, T. (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Digitization of supercases is a strategic step to improve the efficiency and security of documents in educational institutions. This study assesses the implementation of increasing digitization of MTS Expga Univa Medan and its impact on the effectiveness of character and document management. This study uses a qualitative approach using data recording techniques through observation, interviews and documents. This study shows that digitization accelerates character distribution, minimizes the risk of document loss, and improves structured archiving systems. However, there are challenges in terms of human resources and digital infrastructure that need to be improved. Communication Digitization is an effective solution in supporting school management and administration in a modern and efficient way.